Identification of Survival-Associated Gene Signature in Lung Cancer Coexisting With COPD - Miao, Ti-wei; Du, Long-yi; Xiao, Wei; Mao, Bing; Wang, Yan; Fu, Juan-juan (Frontiers in Oncology, 2021)
Background: Chronic obstructive pulmonary disease (COPD) and lung cancer often coexist and are associated with a worse prognosis. Thousands of biomarkers related to the survival of lung cancer have been investigated. However, the biomarkers which can predict survival of COPD coexisting with lung cancer is currently lacking. Therefore, the present study aimed to develop a novel gene signature to predict the prognosis of patients with COPD coexisting lung cancer. Method: RNA-sequence data of lung cancer and healthy control and relevant clinical information of lung cancer were obtained from The Cancer Genome Atlas (TCGA). Differently expression genes (DEGs) were screened by R language. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) were performed. The Cox regression analysis was applied to screen survival-associated DEGs and construct a survival-associated gene signature. Results: seventy COPD coexisting with lung cancer and 108 healthy control were included for further analysis. 2424 DEGs were identified in patients with COPD coexisting lung cancer compared to healthy controls. The biological process was primarily associated with channel activity, passive transmembrane transporter activity, microtubule motor activity. KEGG pathways were mainly enriched in the Neuroactive ligand-receptor interaction, Cell cycle, Staphylococcus aureus infection. nine DEGs were related to survival according to univariate Cox regression analysis. The multi-variate Cox proportional hazards analysis established a survival-associated gene signature consisting of CEACAM5, RASAL1, CSTL1, CNGB1 and SLC4A3. The patients could be divided into high-risk and low-risk groups according to five-gene signature. The high-risk group in gene signature had a worse survival time and area under ROC curve was 0.975. Additionally, multivariate Cox regression analysis revealed that the prognostic power of the five-gene signature is independent of clinical factors. Conclusion: A survival-associated gene signature was established by the multi-variate Cox regression analysis for COPD coexisting with lung cancer, which might predict survival of patients with COPD coexisting with lung cancer.